Penerapan Nilai Sila Ke 1 Pancasila Kepada Anak-Anak Melalui Pembelajaran Tahsin Al-Qur’an dan Praktik Sholat - Rihma Amalia Muslim; Rima Melati Suci; Riva Nuryanti; Salsa Dila Juwita; Suci Nuraeni; Syeni Adinda Bren; Thoriq Muhammad Hamzah; Tiara Seftian; Zahra Silmi Dzakiyyah; Dian Herdiana (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This activity is an actualization of the values ​​of Pancasila, the 1st principle of "Belief in One Supreme God", the first principle which gives freedom for the people to choose religion without any coercion at all, contributing to each other to take care of each other, the implementation of the first Pancasila principle can also be done by means of character education, one of which is to arouse the enthusiasm of children to study religious knowledge, which is carried out in the area of ​​each group member, teaches about the practice of praying, tahsin Al-Qur'an in the environment of each group member. The method applied to the implementation of this socialization is society participatory, which is to engage directly with the community (children from the age of 3-15 years). This study aims for children to know how to read the Qur'an properly according to reading guidance, be able to understand well the practice of praying, facilitate prayer reading and justify movements in prayer in accordance with Islamic law with the aim of implementing the first principle of Pancasila practice, if children have learned from an early age, then what is taught will still be closely attached to adulthood. Instilling the soul that we should be religious so that life is directed and children become the successors of the nation who have good morals, high social spirit and are able to lead themselves and others according to the teachings of their respective religions